2020
DOI: 10.1002/acn3.51053
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated axonal dysfunction in seropositive and seronegative primary Sjögren’s syndrome

Abstract: Objective: The present study investigates the peripheral neuropathy in Primary Sj€ ogren's syndrome (pSS) using the nerve excitability test to further elucidate how peripheral nerves are affected by the autoantibodies. Methods: Each patient received clinical evaluation, examination for anti-SSA/Ro and anti-SSB/ La antibodies titer, paired motor and sensory nerve excitability test, thermal quantitative sensory test (QST), and nerve conduction study (NCS). Results: A total of 40 pSS patients wasenrolled. Motor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…A quite interesting finding was the increased number of mixed peripheral neuropathy, meaning that a demyelinating mechanism was associated with axonal damage, which is consistent with previously published data [40]. Myelin sheath damage is documented in pSS in the context of both vasa nervorum inflammation and autoimmune mediated mechanisms [41,42]. Only one study had priorly identified a majority of demyelinating pattern in Sjögren's peripheral neuropathy, reporting subclinical demyelination in 24% of the patients [43].…”
Section: Discussionsupporting
confidence: 87%
“…A quite interesting finding was the increased number of mixed peripheral neuropathy, meaning that a demyelinating mechanism was associated with axonal damage, which is consistent with previously published data [40]. Myelin sheath damage is documented in pSS in the context of both vasa nervorum inflammation and autoimmune mediated mechanisms [41,42]. Only one study had priorly identified a majority of demyelinating pattern in Sjögren's peripheral neuropathy, reporting subclinical demyelination in 24% of the patients [43].…”
Section: Discussionsupporting
confidence: 87%
“…The serum AQP4-IgG was easier to bind to the target antigen on the foot of astrocytes in the CNS and gave rise to an inflammatory cascade reaction that resulted in brain injury and neurological dysfunction. Another explanation is that the anti-SSA/Ro antibody combined with the cell surface SSA antigen causes nerve pathological changes, including the degeneration of axons and the loss of myelinated fiber in certain circumstances (Tani et al, 2020). Other studies found that "the anti-SSA/Ro antibody up-regulates the expression of inflammatory cytokines by triggering pathways of tumor necrosis factor (TNF) converting enzyme, TNF-α and nuclear factor-κB (NF-κB)" (Lisi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The study selection process is illustrated in the PRISMA chart (Figure 1). All of the 49 studies that met our inclusion criteria [19–67] were of an observational nature. The majority of the papers were published by research teams that included both rheumatologists/internists and neurologists ( n = 31) followed by research teams that included either only rheumatologists/internists ( n = 12) or only neurologists ( n = 6).…”
Section: Resultsmentioning
confidence: 99%